The Effect of Green Intellectual Capital and Organizational Environmental Management on Green Organizational Identity and Its Impact on Green Competitive Advantage - Rosmawati, Wati; Murwaningsari, Etty (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
This study aims to examine the effect of Green Intellectual Capital and Organizational Environmental Management on Green Organizational Identity and its impact on Green Competitive Advantage. This research also aims to prove Green Organizational Identity as an intervening variable. This study uses a questionnaire to managers, assistant managers, company staff using an online Google form via a distributed link. The number of respondents we used was 115 samples collected and analyzed using SPSS. The results showed: From the results of research and research discussion, the following conclusions can be drawn: that there is a direct significant effect of Green Intellectual Capital (GIC) on Green Organizational Identity (GOI). Directly there is a significant influence of Organizational Environmental Management (MLO) on Green Organizational Identity (GOI). Directly there is a significant effect of Green Intellectual Capital (GIC) on Green Competitive Advantage (GCA). Directly there is a significant effect of Organizational Environmental Management (MLO) on Green Competitive Advantage (GCA). Directly there is no significant effect Green Organizational Identity (GOI) against Green Competitive Advantage (GCA). Indirectly, GIC through GOI does not have a significant effect on GCA. Indirectly MLO through GOI has a significant effect on GCA MLO through GOI has a significant effect on GCA. The limitations in this study are: this study only uses a small sample of 115 respondents, so that for the next research it can add more samples. The next researcher can use respondents in the managerial level who actually work for companies that produce waste. Implications: There is support from all parties, including government, government, and academia to raise awareness to play a role in sustainable development for the future. Through increasing insights to pay attention and consider the environment.